Political elites in East Central Europe : paving the way for "negative Europeanisation"? - Gallina, Nicole, 1974- (Opladen ; Farmington Hills, MI : Budrich UniPress, 2008)
"This monograph is a major survey of East Central European (ECE) political elites and concentrates on Czech Republic, Slovakia, Hungary and Poland. It is grounded within classic elite theory slightly adapted to ECE necessities. More practically, the book examines political elite composition and identifies political elite fragmentation in ECE." "The author questions that East Central European political elites have incorporated democratic values and conduct. The main argument is that there is a significant gap between the formal democratic ECE institutions and political elite behaviour. This gap has different dimensions which are relevant at the domestic level and also cause problems at the EU Level. Ultimately, the political elite-institution gap questions democratic political achievements after 1989. In providing a major analysis of ECE political elite structure and conduct the book points to the most urgent challenges of ECE political systems - the reform of the political elite."--BOOK JACKET.
Includes bibliographical references (pages 209-224).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Europe, Central -- Politics and government -- 1989-; Europe, Eastern -- Politics and government -- 1989-; Political culture -- Europe, Central; Political culture -- Europe, Eastern; Elite (Social sciences) -- Europe, Central; Elite (Social sciences) -- Europe, Eastern; Europe centrale -- Politique et gouvernement -- 1989-; Europe de l'Est -- Politique et gouvernement -- 1989-; Élite (Sciences sociales) -- Europe centrale; Élite (Sciences sociales) -- Europe de l'Est.; Elite (Social sciences); Political culture; Politics and government; Central Europe; Eastern Europe; Politische Elite; Osteuropa; Politisk kultur -- Östeuropa.; Eliter -- Östeuropa.; Östeuropa -- politik och förvaltning.; Since 1989